2007
DOI: 10.1111/j.1600-0846.2007.00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation of erythema and pigmentation induced by ultraviolet radiations of different wavelengths

Abstract: Two MED of UVA produced far prolonged erythema and pigmentation than UVB. For UVA, UVA 1 and BBUVA showed similar intensity and time course of skin reaction. For UVB, erythema and pigmentation produced by NBUVB were milder in intensity and shorter in time course than those by BBUVB. These results would provide standard data on time courses and intensity of skin color changes by different UV wavelengths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The acute side effects of NBUVB include erythema, edema, blistering, pruritus, and reactivation of herpes simplex virus, but these usually resolve within several days30. Although previous studies have described a possibility of photoaging and carcinogenesis in association with NBUVB, there is still no evidence that this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…The acute side effects of NBUVB include erythema, edema, blistering, pruritus, and reactivation of herpes simplex virus, but these usually resolve within several days30. Although previous studies have described a possibility of photoaging and carcinogenesis in association with NBUVB, there is still no evidence that this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…IPD occurs during the first minutes of exposure to UVA, and then fades within few hours 6 , 8 . PPD appears within hours of higher doses of UVA exposure and persist up to several days or weeks 7 , 9 . DT develops over 3–7 days after UVB exposure, and then remains for weeks 10 .…”
Section: Cosmetic Tanningmentioning
confidence: 99%
“…Sunbeds have several times higher UVA fluence rates than found in solar radiation under relevant conditions, 19 , 20 and, due to this, IPD and PPD are pronounced after sunbathing. Additionally, under certain conditions UVA-induced pigmentation lasts longer than UVB-induced DP 9 . This can be partly explained by the facts that UVB-induced tanning is located in the upper layers of the epidermis, while UVA-induced tanning is primary localized in the basal cell layer 11 .…”
Section: Cosmetic Tanningmentioning
confidence: 99%
“…In particular, sulforaphane, which is converted from a major glucosinolate in broccoli/broccoli sprouts (Zhang et al 1992;Clarke et al 2008), has been demonstrated to be not only effective in preventing chemically induced cancers in animal models (Fahey et al 1997;Fahey et al 2002;Zhang et al 1994;, but also in inhibiting the growth of established tumors (Singh et al 2004b;Jackson and Singletary 2004). The down-regulation of NF-κB function by sulforaphane treatment has been reported in prostate and colon cancer cells as well (Choi et al 2007;Xu et al 2005;Jeong et al 2004;Khor et al 2006). Based on this study, they concluded that combination of sulforaphane with TRAIL would be a promising strategy for targeting pancreatic TICs (Kallifatidis et al 2009).…”
Section: Sulforaphanementioning
confidence: 95%